State-space methods for time series analysis : theory, applications and software /: theory, applications and software. (2018) - (Banker), Casals, Jose; Garcia-Hiernaux, Alfredo; Jerez, Miguel; Sotoca, Sonia; Trindade, A. Alexandre
No abstract available